Nitrogen contribution of four legumes to a subsequent maize crop - Haque, I.; Jutzi, S.C. (International Livestock Centre for Africa, 1985)
Reports on the Nitrogen contribution of one forage and three grain legumes, viz, vetch (Vicia villosa), wheat, faba beans, peas & lentils, to a subsequent maize crop in the Ethiopian highlands.